Tax Audit Signals Contribute to the Diminishing of Tax Haven Beneficiary Firm Value - Tjondro, Elisa; Valentina, Gracia Pulcheria; Gunawan, Sianne Ivana; Dewantoro, Yohannes (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 2 (2022), 2022)
The purpose of this study is to obtain an overview of the interaction of the tax havens' use and disclosure of tax audits and the impact of both on the firm value before the tax rate reduction period. The sample is Indonesia-listed firms in agriculture, basic industry and chemical, miscellaneous industry, and consumer goods sectors for 2015 – 2019. This research uses panel data and weighted least square regression. The findings indicate that using tax havens through subsidiaries is associated with increased firm value. In contrast, firms that have subsidiaries in a tax haven and disclose the result of tax audits are associated with a decrease in firm value. This research, to our knowledge, is the first research that combines the impact of tax haven utilization and tax audit disclosure on firm value in Indonesia. Keywords : tax haven utilization, tax audit disclosure, firm value, tax haven subsidiaries, signalling theory